Evaluation von Entscheidungsbaummodellen des maschinellen Lernens für das akute Leberversagen nach Reanimation = Evaluation of decision-tree models of machine learning for the prediction of acute liver failure after resuscitation - Luckscheiter, André Hermann; Zink, Wolfgang; Thiel, Manfred; Viergutz, Tim (Anästhesiologie & Intensivmedizin, 2022)
Background: Patients after cardiac arrest developing acute liver failure (ALF) show higher fatality rates and worse outcomes. As machine learning is able to support physicians in their decision-making with the help of big data in health records, the aim of this study is to evaluate decision-tree models for the prediction of ALF after resuscitation.